A Shared Path: Co-occurrence and Clinical Implications of Celiac Disease and Type 1 Diabetes Mellitus - Florczak, Wojciech; Śnieżna, Joanna; Dziewic, Jakub; Dzwonnik, Karol; Domino, Wiktoria; Zelik, Urszula; Trestka, Gabriela; Przygoda, Maria; Włodyka, Jagienka; Stępień, Kamila; et al. (Quality in Sport, 2025)
Introduction: Celiac disease (CeD) and Type 1 diabetes mellitus (T1DM) are autoimmune diseases that sometimes co-occur in genetically predisposed people. Both diseases share common genetic factors, such as human leukocyte antigens: HLA-DQ2 and HLA-DQ8. Apart from that, they share environmental factors such as gluten exposure, viral infections, and alterations in gut microbiota composition. CeD is a gluten-induced disease resulting in inflammation and impaired absorption of the nutrients, leading to malnutrition. In T1DM, β-cells in the pancreatic tissue are destroyed during the T-cell mediated reaction, which leads to impaired insulin production and development of insulin deficiency which leads to hyperglycemia and chronic complications. Materials and methods: This study is based on a review of multiple articles and prospective studies we managed to find online in the PubMed database. Aim of the study: The aim of the study is to investigate the clinical implications of T1DM and CeD, focusing on the importance of early screening for CeD in patients with T1DM and evaluate the challenges in the management of both diseases simultaneously. Additionally, the study highlights the potential benefits of a personalized approach to treatment. Conclusions: The co-occurrence of CeD and T1DM is common and it’s determined by shared genetic, immune, and environmental factors. Early screening and diagnosis are very important regarding the management strategies for these conditions. Gluten free diet (GFD) is the main treatment for CeD, but its adherence may be challenging, especially in T1DM patients who already face many restrictions on a daily basis. Personalized treatment approaches seem to be essential for simultaneously managing and optimizing CeD and T1DM. However, the lower compliance to GFD among T1DM patients suggests the need for further research to provide support for long-term management of both T1DM and CeD.